Horizontal Transition of Expertise - Gegenfurtner, Andreas; Gruber, Hans; Lehtinen, Erno; Säljö, Roger (Frontline Learning Research, 2024)
Expert performance in a domain is often defined as maximal adaptation to stable task constraints. This definition is useful when analyzing the vertical transition when novices become experts. However, many workplaces undergo considerable changes and, thus, task constraints change as well. In this paper, a complementary conceptualization of expertise is offered, one that focuses on expert performance as recurring adaptation to dynamic task constraints. This definition is useful when analyzing the horizontal transition when experts adapt to dynamically changing work contexts. Using the documentary method, the aim of the present study was to analyze cases of horizontal transitions based on qualitative biographical interview data from five experts reconstructing different types of adaptation to technological change in their domains that they have experienced. Implications for studying horizontal transitions at dynamic worksites are discussed.